Retrospective clinical and genetic analysis of COL6-RD patients with a long-term follow-up at a single French center - Morel, Victor; Audic, Frédérique; Tardy, Charlotte; Verschueren, Annie; Attarian, Shahram; Nguyen, Karine; Salort-Campana, Emmanuelle; Krahn, Martin; Chabrol, Brigitte; Gorokhova, Svetlana (Frontiers in Genetics, 2023)
Collagen type VI-related dystrophies (COL6-RD) are rare diseases with a wide phenotypic spectrum ranging from severe Ullrich's congenital muscular dystrophy (UCMD) to much milder Bethlem myopathy (BM). Both dominant and recessive forms of COL6-RD are caused by pathogenic variants in three collagen VI genes (COL6A1, COL6A2 and COL6A3). The prognosis of these diseases is variable and difficult to predict during early disease stages, especially since the genotype-phenotype correlation is not always clear. For this reason, studies with long-term follow-up of patients with genetically confirmed COL6-RD are still needed. In this study, we present phenotypic and genetic data from 25 patients (22 families) diagnosed with COL6-RD and followed at a single French center, in both adult and pediatric neurology departments. We describe three novel pathogenic variants and identify COL6A2:c.1970-9G>A as the most frequent variant in our series (29%). We also observe an accelerated progression of the disease in a subgroup of patients. This large series of rare disease patients provides essential information on phenotypic variability of COL6-RD patients as well as on frequency of pathogenic COL6A gene variants in Southern France, thus contributing to the phenotypic and genetic description of Collagen type VI-related dystrophies.